Peran Partai Oposisi Dalam Sistem Ketatanegaraan Konvensional dan Islam - Marsudi Marsudi; Siti Ngainnur Rohmah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Opposition parties still have a negative image in Indonesian society, so parties that lose in elections are often reluctant to call their party an opposition party. This is due to the dark history of the Indonesian nation. Islam stipulates deliberation as one of the Islamic rules of life and obliges a leader to hold deliberations and obliges his people to criticize what his leader, known as the opposition, has done. The purpose of this research is to find out the role of the opposition parties in the conventional and Islamic constitutional systems. This research uses the library method. Research data comes from sources of literature and journals that are relevant to the title above, either directly or indirectly. The results of the discussion show that the role of the opposition party in the conventional and Islamic constitutional system is as a loyal opposition or can be called a party that supports the government but remains critical of pro-people government policies and acts as a check and balance or as a supervisor and counterweight in government. In essence, humans are in the wrong place and make mistakes so the party as a forum for people's aspirations should be tasked with overseeing the performance of the government. As for Islam, it is manifested in the form of Amar Ma'ruf Nahi Munkar.Keywords: Opposition; state administration; Islam; conventional AbstrakPartai oposisi masih memiliki image negatif dalam masyarakat Indonesia, sehingga partai yang kalah dalam pemilu seringkali enggan menyebut partainya sebagai partai oposisi. Hal ini dikarenakan sejarah bangsa Indonesia yang kelam. Islam menetapkan musyawarah sebagai salah satu kaidah hidup yang islami dan mewajibkan seorang pemimpin untuk melakukan musyawarah serta mewajibkan umatnya untuk mengkritisi apa yang telah dilakukan pemimpinnya yang dikenal dengan oposisi. Tujuan penelitian ini untuk mengetahui bagaimana peran partai oposisi dalam sistem ketatanegaraan konvensional dan Islam. Penelitian ini menggunakan metode pustaka. Data penelitian berasal dari sumber kepustakaan dan jurnal yang ada relevansinya dengan judul di atas baik langsung maupun tidak langsung. Hasil dari pembahasan menunjukan bahwa peran partai oposisi dalam sistem ketatanegaraan konvensional dan Islam adalah sebagai loyal oposisi atau dapat disebut sebagai partai yang mendukung pemerintah namun tetap kritis terhadap kebijakan pemerintah yang pro rakyat dan berperan sebagai chek and balance atau sebagai pengawas dan penyeimbang dalam pemerintahan. Pada hakekatnya manusia tempatnya salah dan khilaf sehingga partai sebagai wadah aspirasi rakyat hendaknya bertugas mengawasi kinerja pemerintah. Adapun dalam Islam diwujudkan dalam bentuk Amar Ma’ruf Nahi Munkar.Kata kunci: Oposisi; Ketatanegaraan; Islam; Konvensional